Archaeology in the Era of Powassan and Expanding Tick-Borne Infection: Strategies for Prevention. Issue 4 (November 2015) - Singer, Merrill; Bulled, Nicola
Abstract: Archaeologists face a long list of job-related health risks. In recent decades, these health threats have increased because of the expanded ranges of various tick species, the growing number of human tick-borne diseases, the ability of ticks to harbor and simultaneously transmit multiple pathogens, and the spread to humans of zoonotic tick-borne diseases that have a high fatality rate, including the encephalitis-causing Powassan virus. This paper assesses the health risk that ticks pose to archaeologists working in infested areas, discusses the behaviors that put archaeologists at highest risk, and presents a set of recommendations for reducing potential harm.